1989
DOI: 10.1038/icb.1989.39
|View full text |Cite
|
Sign up to set email alerts
|

Gm allogenotype distribution and lack of HLA‐DR, Gm interaction in SLE and CREST/PSS

Abstract: Summary The distribution of Gm allogenotypes (Gm allotypes identified by IgCH restriction fragment length polymorphism (RFLP) analysis) was compared in 66 systemic lupus erythematosus (SLE) patients, 38 CREST/PSS patients and 56 healthy controls. Patient/control comparison showed that Gm homozygosity was increased in the CREST/PSS group (/'<0-05) but not in the SLE group. HLA-DR5 is significantly increased in frequency in this series of CREST/PSS patients compared to controls (f<0-001), and log linear regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1991
1991
1995
1995

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The association of imrnunoglohulin allotypes with susceptibility to systemic lupus erythematosus (SLE) has been reported in different ethnic populations (1-4). A Gm allotype relationship with SLE was found, in association with HLA antigens, in patients in Hungary and Australia (3,4); other studies have demonstrated no such Gm/HLA association (5). In Caucasian SLE patients, we have observed an increased frequency of Gm 1,3,17;5,13,21 and a decreased frequency of Gm 3;5,13 (the latter was thus associated with resistance to the disease) (1).…”
mentioning
confidence: 99%
“…The association of imrnunoglohulin allotypes with susceptibility to systemic lupus erythematosus (SLE) has been reported in different ethnic populations (1-4). A Gm allotype relationship with SLE was found, in association with HLA antigens, in patients in Hungary and Australia (3,4); other studies have demonstrated no such Gm/HLA association (5). In Caucasian SLE patients, we have observed an increased frequency of Gm 1,3,17;5,13,21 and a decreased frequency of Gm 3;5,13 (the latter was thus associated with resistance to the disease) (1).…”
mentioning
confidence: 99%